Rahn (Gadai) dalam Perspektif Fikih Muamalah, Kompilasi Hukum Ekonomi Syariah (KHES), dan Hukum Perdata - Junitama, Calvin Alief; Rahmawati, Elvira Dwi; Karina, Murtila (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2022)
Pawn in Islam is called rahn. Pawning is an activity to pawn goods as collateral for a debt transaction carried out. A person who mortgages an item (rahin) to a murtahin person, then the item remains the property of the guarantor (rahin). As a result, a guarantor (murtahin) may not use or sell the collateral before obtaining permission from the guarantor. As for a murtahin, he can ask for money from the rahin if it is used for the maintenance of the rahin's property if maintenance is needed on the item. In this day and age, this pawn has become one of the solutions to the urgent need for money which is needed by the community. In muamalah fikih and KHES, the pawn is called rahn. While in civil law the pawn is called a pand.